2015
DOI: 10.1007/s13402-015-0232-x
|View full text |Cite
|
Sign up to set email alerts
|

The bone marrow metastasis niche in retinoblastoma

Abstract: The various BM metastasis-related molecular changes identified to date may be instrumental for a better diagnosis, prognosis and classification of Rb patients, as well as for the development of novel comprehensive (targeted) therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 95 publications
(87 reference statements)
0
14
0
Order By: Relevance
“…Other ways through which tumor cells may spread include local tissue invasion and direct seeding into body cavities. Which way tumor cells choose to spread depends on the site of tumor initiation, the aggressiveness of the tumor cells, extrinsic signals and intrinsic tumor micro-environmental conditions including direct cell-cell and cell-matrix interactions within a tumor niche and the presence of paracrine factors mediating the formation of new vessels [ 5 ]. It has been found that solid tumors frequently induce angiogenesis and lymphangiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Other ways through which tumor cells may spread include local tissue invasion and direct seeding into body cavities. Which way tumor cells choose to spread depends on the site of tumor initiation, the aggressiveness of the tumor cells, extrinsic signals and intrinsic tumor micro-environmental conditions including direct cell-cell and cell-matrix interactions within a tumor niche and the presence of paracrine factors mediating the formation of new vessels [ 5 ]. It has been found that solid tumors frequently induce angiogenesis and lymphangiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The role of matrix metalloproteinases (MMPs) and dipeptidyl peptidases (DPPs) in invasive and metastatic processes has amply been documented [ 1 , 7 9 ]. MMPs are zinc- and calcium-dependent peptidases essential for ECM reorganization.…”
Section: Introductionmentioning
confidence: 99%
“…Micro-environmental factors may have profound effects on cancer cells, including their metastatic behavior [1][2][3]. Since metastasis is one of the most crucial factors determining the survival of cancer patients, ample attempts have been made to identify key molecular mediators that control metastasis.…”
Section: Introductionmentioning
confidence: 99%